The Multilateral Debt Relief Initiative (G-8 Proposal) and Its Implications for the Fund : Further Considerations. (Policy Papers; Policy Paper ;, 2005)
The Executive Board held an informal seminar on September 21, 2005 to discuss possible implementation modalities for the G-8 debt relief proposal. On September 24, 2005, the International Monetary and Financial Committee supported providing 100 percent cancellation of debt owed by HIPCs to the Fund, and considered that this would provide significant additional resources for countries' efforts to reach the Millennium Development Goals and reinforce long-term debt sustainability.